MINSKY MEETS PORTER - Erkut, Burak (Technical Univ Liberec, 2022)
Hyman P. Minsky and Michael E. Porter have developed theories of economic development independently from each other, both being influenced by Joseph A. Schumpeter in different ways. In this contribution, the author focuses on understanding the similarities and differences between these two approaches based on their epistemological, ontological and ethical-political perspectives, also by identifying how they are related to each other in a particular type of economic development named as 'money-manager capitalism' in Minsky's framework and 'wealth-driven competitive stage' in Porter's. The approach starts by describing the Porterian and Minskyan perspectives, moves on to analyzing them from their epistemological, ontological and ethical-political perspectives, and it also questions how these two phenomena are related by pointing out to the common Schumpeterian perspectives as well as fundamental differences between the two. The contribution concludes by stating that even though differences are present, both approaches are Schumpeterian in their own way - and describe a similar end to competitive development, one that is based on managing accumulated wealth. This is related to two distinctive areas in economics and administrative sciences: Firstly, it shows how the two scholars' ideas are related with a possible source of influence, contributing to history of economic thought. Secondly, it shows the fate of economies once they innovate and become innovation driven; over time, income generated from innovation becomes a source of concern, and influences the risk-taking behavior of the economic system for the sake of protecting the income. In this way, the approach contributes to countries' competitive positions and how two important scholars of economics and administrative sciences observe the start of the decline.
Keywords: Minsky; Porter; Schumpeter; competitive advantage of nations; evolution of capitalism; Porter's diamond